2006
DOI: 10.1634/stemcells.2005-0589
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Infusion of CD133 + and CD133 CD34 + Selected Autologous Bone Marrow Progenitor Cells in Patients with Chronic Ischemic Cardiomyopathy: Cell Isolation, Adherence to the Infarcted Area, and Body Distribution

Abstract: Central issues in intracoronary infusion (ICI) of bone marrow (BM)-cells to damaged myocardium for improving cardiac function are the cell number that is feasible and safe to be administrated as well as the retention of cells in the target area. Our study addressed these issues in eight patients with chronic ischemic cardiomyopathy undergoing ICI of selected BM-progenitors. We could immunomagnetically isolate 0.8 +/- 0.32 x 10(7) CD133(+) cells and 0.75 +/- 0.24 x 10(7) CD133(-)CD34(+) cells from 310 +/- 40 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 25 publications
3
52
1
Order By: Relevance
“…According to Davy et al [16] enrichment of autologous bone marrow CD34 + stem cells could increase the efficacy of treatments in clinical settings. Despite the fact that CD34 + cells have been the selected option for heart repair, there are also some reports of CD133 + cells applied in clinical trials showing improvement of myocardial viability and local perfusion of the infarcted zone [17][18][19][20][21][22]. However, none of these studies have shown de novo formation of cardiac muscle.…”
Section: Introductionmentioning
confidence: 99%
“…According to Davy et al [16] enrichment of autologous bone marrow CD34 + stem cells could increase the efficacy of treatments in clinical settings. Despite the fact that CD34 + cells have been the selected option for heart repair, there are also some reports of CD133 + cells applied in clinical trials showing improvement of myocardial viability and local perfusion of the infarcted zone [17][18][19][20][21][22]. However, none of these studies have shown de novo formation of cardiac muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The SDF-1/CXCR4 pathway is critical during embryogenesis for hematopoietic, vascular development, and cardiac development. It has been reported that 1) cells expressing markers of hematopoietic stem cells or EPCs express CXCR4; 2) vascular endothelial growth factor (VEDF) induces the expression of VEGF and induces angiogenesis in vivo [13][14][15][16][17]. SDF-1 and its receptor CXCR4 are crucial for bone marrow retention of hematopoietic stem cells and are involved in cardiogenesis and recruitment of endothelial progenitor cells to sites of ischemic tissue [18].…”
Section: Mechanisms Of Repairmentioning
confidence: 99%
“…After acute ischemic myocardial injury, serum stoma cell derived factor-1 levels rise significantly, and this chemokine appears to be one key homing signal that regulates homing of stem and progenitor cells to the ischemic myocardium. In patients with chronic ischemic cardiomyopathy, however, local homing signals may not be as intense as in the early post-infarction phase, and therefore the coronary route might not be optimal for cell engraftment [13].…”
Section: Morbid State and Homingmentioning
confidence: 99%
“…The extent of retention of the delivered cells was documented to be rather low with recent studies suggesting that more than 90% are lost partly because of necrosis and apoptosis in the ischaemic myocardium following their delivery by intramyocardial, retrograde transvenous, intracoronary or systemic routes (Terrovitis et al, 2010;Aicher et al, 2003;Goussetis et al, 2006). One means of overcoming this limitation would be to increase the survival of transplanted cells, thus avoiding the impractical and costly alternative of delivering large excesses of stem cells into the injured myocardium.…”
Section: Survivalmentioning
confidence: 99%